Do changes in network structure explain why unemployment damages health? Evidence from German panel data - Krug, Gerhard; Prechsl, Sebastian (Social science & medicine, 2022)
We use German panel data and apply fixed effects regressions to test whether changes in social network size or composition explain why unemployment harms individuals’ health. We consider whether the number of weak ties, the number of strong ties, the share of relatives or the share of unemployed individuals among strong ties mediate the negative relation between unemployment and health. We look at various health and health behavior outcomes, such as self-rated health, mental health, physical health, the number of doctor visits and the number of cigarettes smoked. We find no evidence that structural features of the social network play a role in mediating the health-damaging effect of unemployment. We conduct a variety of supplementary analyses that support and extend our results, including mediation tests for emotional support and contact intensit
Keywords: unemployment; social networks; panel data; fixed effects regression; mediation; contact frequency; social support; Diversity